Anti-Centromere Antibody Positivity in a Patient with Generalized Morphea - Fumi Miyagawa (Case Reports in Dermatology, 2018)
We report the case of a 45-year-old female with generalized morphea (GM), who exhibited positivity for the anti-centromere antibody (Ab). She frequently developed multiple sclerotic skin lesions, whose histological findings were compatible with morphea. She demonstrated favorable responses to topical and oral steroids. Cases of GM associated with systemic sclerosis (SSc)-specific Abs (anti-Scl-70 Ab, anti-centromere Ab, and anti-RNA polymerase III Ab) have rarely been reported. The previously reported GM cases involving anti-SSc-specific Abs exhibited some skin manifestations of SSc, such as nailfold capillary changes. However, our case did not show any signs of SSc or limited cutaneous SSc. More cases are needed to clarify whether GM with SSc-specific Abs leads to SSc.